ANALYSIS OF THE INFLUENCE OF FINANCIAL LITERACY AND DIGITAL LITERACY ON THE DECISION TO USE DANA E-WALLET - Cahyo Pramono (Jurnal Apresiasi Ekonomi, 2026)
This study aims to determine the effect of Financial literacy and digital literacy on Fintech Payment on the Use of Funds. The number of samples used was 90 people, with a purposive sampling method. This study uses a quantitative research method processed through SPSS Version 25. The data analysis technique applied is multiple linear regression. The results of the analysis answer that Financial literacy has a positive and significant effect on Fintech Payment T count Financial literacy of 3.481> 1.661 and significance of 0.001 1.661 and significance of 0.002 F table 23.967> 0.20 at a significance of 0.000